2019
DOI: 10.1111/jwas.12638
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous probiotic bacteria modulate intestinal microbiota of Pirarucu, Arapaima gigas

Abstract: This study aimed to investigate the ability of two probiotic strains (Lactococcus lactis subsp. lactis and Enterococcus faecium) to colonize Arapaima gigas intestines and their competence in modulating gut microbiota, morphology, and immunological status. A total of 135 A. gigas (58.86 ± 10.25 g) were divided into three treatments: (a) fish fed a diet containing L. lactis subsp. lactis at 1 × 108 CFU−1, (b) fish fed a diet containing E. faecium at 1 × 108 CFU−1, and (c) fish fed a diet nonsupplemented with pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
3
0
2
Order By: Relevance
“…A capacidade de inibir o crescimento de patógenos é uma característica importante para a seleção de probióticos no ramo da aquicultura [60][61][62]. Diversos estudos já demonstraram a capacidade das BAL em inibir micro-organismos patógenos Gram positivos e negativos [15,19,21,63], corroborando com os achados deste trabalho.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A capacidade de inibir o crescimento de patógenos é uma característica importante para a seleção de probióticos no ramo da aquicultura [60][61][62]. Diversos estudos já demonstraram a capacidade das BAL em inibir micro-organismos patógenos Gram positivos e negativos [15,19,21,63], corroborando com os achados deste trabalho.…”
Section: Resultsunclassified
“…Normalmente, estes micro-organismos passam por uma triagem in vitro para avaliar o seu potencial probiótico, que inclui caracterização fenotípica, bioquímica, e mais recentemente molecular [14,15]. Além disso, são necessários testes de antagonismo frente à patógenos, resistência a antimicrobianos, entre outros.…”
Section: Introductionunclassified
“…Several studies have reported the benefits of the use of autochthonous lactic acid bacteria for aquaculture (Dias et al, 2018;Pereira et al, 2019;Jatobá et al, 2017;Sousa et al, 2019;Yamashita et al, 2020). Among the bacteria with probiotic potential, Enterococcus faecium stands out because of its ability to completely colonize the intestinal tract of the host when compared with heterotrophic bacteria and which is most likely related to its rapid growth rate in the intestine (Dias et al, 2019;Souza et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro assays can aid in the selection of autochthonous bacteria with probiotic potential, determining their survival in different physiological conditions as well as their inhibitory capacity against pathogens (Dias et al, 2019;Pereira et al, 2019;Paixão et al, 2020;Qi et al, 2020;Sousa et al, 2019). Some studies have reported positive results for both in vitro and vivo assays using autochthonous probiotic bacteria in aquaculture, such as Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The study also showed that gene expression data can help explain some of the mechanisms behind the benefits of using probiotics in fish feeds, namely on fish intestinal morphology, immunity, and disease resistance. Similarly, do Vale Pereira, Pereira, Soares, Mouriño, and Merrifield () showed that probiotic bacteria can modulate the gut microbiome, morphology, and immune status of Pirarucu ( Arapaima gigas ). In addition to specific fish species effects, probiotic strain, and culture settings where probiotics are used, the timing of their supplementation is also of importance for the successful use of probiotics.…”
Section: Disease and Health Managementmentioning
confidence: 95%